ASPECT NEUROLOGICAL ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD) - Setyawan, Agung Budi (Universitas Wijaya Kusuma Surabaya, 2010)
Until now there is no theory that says the exact cause of ADHD, but some theories say there are various contributing factors, including: genetic, minimal brain damage, neurobilogi, neurokimiawi, psychosocial, food, et cetera. In the last decade considerable amount of research that proves that neurological factors have a role and a significant influence on the development of ADHD. Thats why understanding the neurological aspect of ADHD is needed to be done as early handling and seholistik possible so that it can reduce the negative impacts that can occur both in children with ADHD, parents, schools, and communities.Â